The development of autonomous examination paper application: a case study in UiTM cawangan Perlis / Noorfaizalfarid Mohd Noor, Nadhirah Mohd Napi and Izzati Farzana Ibni Amin - Mohd Noor, Noorfaizalfarid; Mohd Napi, Nadhirah; Ibni Amin, Izzati Farzana (UiTM Cawangan Perlis, 2019)
Examination is a vital role to measure the capabilities of students in their learning. Hence, generating question paper in an effective way is a decisive job for educators in educational institution. Using traditional method, it is monotonous and time consuming. Today, Autonomous Examination Paper (AEP) is used to produce exam paper. Many researchers have proposed effective AEPs to be used by educators. This paper aims to investigate about AEP development and to construct AEP in UiTM Cawangan Perlis. As a result, Ad-Hoc Question Paper Application (AQPA) has been developed using Fisher-Yates algorithm to generate questions for exam paper in the university. Evaluation based on Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) reveal that lecturers in the university manage to interact with AQPA and willing to use it as a tool to minimize their workload. However, more improvement must be done on AQPA to be an effective AEP. To conclude, AEP brings significance to educators and can be improved with the latest technology.